Association of long working hours with psychological distress in men with pregnant partners: An observational study from the Japan Environment and Children's Study. - Hidekuni Inadera; Kenta Matsumura; Haruka Kasamatsu; Junko Sakai; Akiko Tsuchida; Japan Environment and Children’s Study (JECS) Group (PLoS ONE)
Background It has been suggested that working long hours affects workers' mental health, although findings have been inconsistent. In this study, we investigated the association of working hours with psychological distress in a population of Japanese men with pregnant partners, using data from the Japan Environment and Children's Study. Methods Data from 44,996 men were analyzed and weekly working hours were classified into six groups. The Kessler Psychological Distress Scale (K6) was used to assess mental health. Each of the six items were assessed on a 5-point scale (0-4), with a total score of 0-24 and higher scores indicating greater psychological distress. A total score of 5-12 was considered to indicate moderate psychological distress and a score of ≥13 to indicate severe psychological distress. To investigate the association of working hours with psychological distress, multinomial logistic regression analysis was performed to calculate odds ratios (ORs) and 95% confidence intervals (CIs). Results The results showed that after adjusting for covariates, weekly working hours was positively associated with moderate and severe psychological distress. Compared with men who worked ≤40 h per week, those who worked >55 to ≤65 h or >65 h per week had significantly higher ORs (95% CIs) for moderate psychological distress, 1.12 (1.03-1.21) and 1.34 (1.24-1.45), respectively, and those working >65 h per week had significantly higher OR, 1.84 (1.47-2.32) for severe psychological distress. For these two outcomes, a significant p for trend (<.0001) was observed in both the crude and adjusted models. Conclusion The results of this study suggest that the greater time constraints resulting from working long hours are associated with psychological distress in Japanese men with pregnant partners.